2018
DOI: 10.1039/c7ra12442b
|View full text |Cite
|
Sign up to set email alerts
|

Structural and impedance spectroscopy characteristics of BaCO3/BaSnO3/SnO2 nanocomposite: observation of a non-monotonic relaxation behavior

Abstract: A BaCO3/BaSnO3/SnO2 nanocomposite has been prepared using a co-precipitation method without adding any additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
(82 reference statements)
3
13
0
Order By: Relevance
“…The XRD peaks of crystallized powders of BaCO 3 agree with the reflection of a pure orthorhombic structure and single phase of BaCO 3 (witherite). This was also evident in the works of Zelati et al 35 and Salehizadeh et al 36 That of CaCO 3 revealed the presence of a single rombohedrical crystal structure correspond- ing to a single calcite phase, which is the most thermodynamically stable form of CaCO 3 predominant at room temperature. Won et al, 37 Harris et al, 38 and Render et al 39 also reported similar phase appearance corresponding to calcite.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 55%
“…The XRD peaks of crystallized powders of BaCO 3 agree with the reflection of a pure orthorhombic structure and single phase of BaCO 3 (witherite). This was also evident in the works of Zelati et al 35 and Salehizadeh et al 36 That of CaCO 3 revealed the presence of a single rombohedrical crystal structure correspond- ing to a single calcite phase, which is the most thermodynamically stable form of CaCO 3 predominant at room temperature. Won et al, 37 Harris et al, 38 and Render et al 39 also reported similar phase appearance corresponding to calcite.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 55%
“…BaSnO3 is used to prepare capacitors because of its characteristic dielectric properties [10]. It is also used as a sensor material for a wide variety of gases, such as CO, Cl2, NOx, O2, CO2, C2H5OH, CH3SH and sensing humidity and liquefied petroleum gas [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These modes are due to the six fundamental vibrations of SnO6 octahedron which has Oh symmetry, in the distorted perovskite structure. The bands found at 561, 190 and 140 cm −1 are due to Raman active v2Eg, v4F1u and v5F2g modes respectively [35].…”
Section: Raman Analysismentioning
confidence: 92%